The Effect of Sharia Economic Festival Education and Financial Literacy on Halal Awareness and the Intention to Use Sharia Financial Products in Indonesia - Bhaswarendra Guntur Hendratri; Kurniawan Kurniawan; Ilza Febrina; Junet Kaswoto; Puti Khairani Rijadi (West Science Interdisciplinary Studies, 2025)
This study investigates the effect of Sharia Economic Festival education and financial literacy on halal awareness and the intention to use Sharia financial products in Indonesia. Employing a quantitative research design, data were collected from 135 respondents using a five-point Likert scale questionnaire. The analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The results demonstrate that Sharia Economic Festival education significantly enhances financial literacy and halal awareness. Financial literacy also has a strong positive effect on halal awareness and directly influences the intention to use Sharia financial products. Moreover, halal awareness emerges as the most influential predictor of consumer intention, highlighting the central role of religious and ethical considerations in the adoption of Sharia-compliant financial services. The findings emphasize the importance of educational interventions, financial knowledge, and awareness-building strategies to strengthen the penetration of Sharia financial products in Indonesia. This study contributes to theoretical understanding and provides practical implications for policymakers, financial institutions, and event organizers seeking to increase public engagement with Islamic finance.